The impact of Lean management on achieving Functional Creativity: An applied study at Taif University - Al-Jaeed, Samia Ayed; Al-Thbaity, Remas Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to know the impact of applying the requirements of lean management on achieving the dimensions of functional creativity at Taif University. The quantitative approach and the questionnaire tool were used to analyze the research variables according to two axes: lean management requirement university’s and the second axis to reveal the availability of functional creativity dimensions (originality, fluency, flexibility, sensitivity to problems) at Taif University, in addition to the impact of the independent variable on the dependent variable. A random sample of (346) individuals out of (3494) of (administrators and academics) at the university was distributed according to demographic variables (gender, nature of work, academic rank, practical experience). (298) questionnaires were retrieved, valid for analysis, at a rate of (86%). The results show that there is a positive influence of one of lean management requirement’s (the change of university culture) on functional creativity. Conducting more future studies on the impact of the remaining dimensions of lean management such as (agility and speed in decision-making) in achieving job creativity are suggested. As well as conducting comparative studies between Taif University and other local and international universities in the application of lean management and its impact on job creativity to benefit from experiences and transfer good practices.